MEMBANGUN SISTEM PERADILAN PIDANA ANAK DI INDONESIA BERBASIS CITA HUKUM PANCASILA - Dwinanda Linchia Levi Heningdyah Nikolas Kusumawardhani (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2022)
A child criminal justice system based on Pancasila legal ideals is needed in resolving children in conflict with the law, because Pancasila is a philosophical study in restorative justice. The juridical study of restorative justice in national legal instruments, which considers and examines the relationship of various laws and regulations relating to restorative justice based on Pancasila legal ideals as a means of dealing with children in conflict with the law. Sociological studies, namely the negative side of imprisonment for children, that the impact of imposing imprisonment on children will cause stigma and this will hinder the future of children. Building an ideal juvenile criminal justice system in dealing with children in conflict with the law based on the ideals of the Pancasila law, the paradigm that must be used is the Pancasila paradigm, which is oriented to the values of